Treatment-Related Mechanisms of Tibetan Medicine Terminalia chebula (TC) Aqueous Extract Against Mouse Gastroenteritis Caused by Yak-Origin Salmonella Determined Using Intestinal Microbiome Analysis and Metabolomics - Dengyu Li; Kaiqin Zhang; Xiaofeng Xue; Zhanchun Bai; La Yang; Jingjing Qi; Sizhu Suolang (Animals)
This study aimed to evaluate the therapeutic effect of Terminalia chebula (TC) on Tibetan yak-origin Salmonella-induced diarrhea and dysentery in mice. The levels of pro-inflammatory cytokines (IL-1β, IL-6, IL-8, and TNF-α), anti-inflammatory cytokines (IL-4 and IL-10), and the oxidative stress markers malondialdehyde (MDA), superoxide dismutase (T-SOD), total antioxidant capacity (T-AOC), reduced glutathione (GSH-PX), and catalase (CAT) in the serum of mice were measured using ELISA kits. Using microbial diversity sequencing and non-targeted metabolomics detection techniques, the relevant mechanisms of TC treatment in a mouse Salmonella infection model were evaluated. The results showed the following: TC can effectively reduce the diarrhea rate; alleviate weight loss caused by Salmonella invasion; reduce the pro-inflammatory cytokines IL-1β, IL-6, IL-8, and TNF-α in serum; and increase the concentrations of the anti-inflammatory cytokines IL-4 and IL-10. TC can improve the body’s antioxidant levels to heal the damage caused by oxidative stress and lipid peroxidation. The histological section results show that TC can significantly improve gastric and intestinal tissue lesions and has no toxic effects on the liver and kidneys. 16S rRNA and ITS sequencing analysis suggests that Lactobacillus, Enterorhabdus, Alistipes (bacterial community), Lodderomyces, Saccharomyces, and Penicillium (fungal community) may be key functional microbial communities in TC. Non-targeted metabolomics also suggests that the antibacterial treatment of dysentery with chebulic acid may be related to regulation of the Ras signaling pathway, long-term potentiation, the MAPK signaling pathway, metabolic pathways, and gut microbiome composition. Conclusion: TC has clear clinical efficacy in treating bacterial diarrhea, presenting anti-inflammatory and antioxidant effects. Its roles in regulating the gut microbiome and metabolic pathways and products were determined as the main reason for its therapeutic effect in a mouse gastroenteritis model caused by Salmonella infection.